2012
DOI: 10.1002/anie.201203389
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Percolative Composites with a High Dielectric Constant and High Conductivity

Abstract: The dielectric constant and electrical conductivity of a composite of two insulators, poly(1,1-difluoroethylene) (yellow) and K(2)CO(3) (white), increased dramatically near the percolation threshold f(c) (f=concentration of K(2)CO(3)). This intriguing phenomenon can be interpreted in terms of interface percolation caused by the formation of chemically activated interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The lower dielectric loss was due to lower loss tangent of (Ba 0.5 Sr 0.4 Ca 0.1 )­TiO 3 , typically ∼0.001–0.002, as well as changes in the physical properties of the PVDF matrix. Wang et al prepared two-phase percolative nanocomposites by using potassium carbonate (K 2 CO 3 ) as insulating fillers . It was found that the permittivity of the composite was enhanced to 2.9 × 10 6 with a loss tangent of 27.5 at 1 kHz near the percolation threshold (23 vol %).…”
Section: Pvdf-based Nanocompositesmentioning
confidence: 99%
“…The lower dielectric loss was due to lower loss tangent of (Ba 0.5 Sr 0.4 Ca 0.1 )­TiO 3 , typically ∼0.001–0.002, as well as changes in the physical properties of the PVDF matrix. Wang et al prepared two-phase percolative nanocomposites by using potassium carbonate (K 2 CO 3 ) as insulating fillers . It was found that the permittivity of the composite was enhanced to 2.9 × 10 6 with a loss tangent of 27.5 at 1 kHz near the percolation threshold (23 vol %).…”
Section: Pvdf-based Nanocompositesmentioning
confidence: 99%
“…[1][2][3] In these polymer nanocomposites, synergistic fusion of polymers and active nano-inclusions gives rise to superior thermal transportation performance, 4 high electrical conductivity or much enhanced dielectric polarization. 5 Interfacial issues between the polymers and nano-inclusions are most dominant in determining the performances of polymer nanocomposites. For instance, the Kapitza thermal resistance at the polymer/nano-inclusion interface seriously limits the maximal thermal conductivity that could be achieved in polymer nanocomposites and even carbon nanotubes 6 or boron nitride 4 of super high thermal transportation properties are employed as nano-inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the percolative compositing strategy can effectively passivate charge traps and reduce the less-conductive areas in pure Co 3 O 4 film, and better guide the charge flow by constructing nanosized charge transport pathways. [28][29][30][31]45] Space-charge limited current (SCLC) tests were carried to determine hole mobility of Co 3 O 4 and Co 3 O 4 -SrCO 3 films. The higher hole mobility can be calculated for Co 3 O 4 -SrCO 3 (6.33 × 10 −2 cm 2 V −1 s −1 ) compared with Co 3 O 4 (1.49 × 10 −2 cm 2 V −1 s −1 ), agreeing well with the c-AFM results (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%